ANALYSIS OF MARKETING CHANNELS AND MARKETING COSTS IN QUAIL EGG FARMING IN BOYOLALI REGENCY - Dwi Rahayu, Ismiati; Lestari, Retna Dewi (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2023)
This study aims to determine the types of quail egg marketing channels in Boyolali Regency and determine the cost of marketing quail eggs in Boyolali Regency. This research was carried out in Boyolali Regency. The selection of breeder sample uses the purposive sample method while the sample of wholesalers, collectors, retailers and consumers uses a purposive method with predetermined criteria. There were 69 samples taken. The results showed that there are 4 marketing channels in Boyolali Regency There are four marketing channels, namely: a) zero level marketing channels: farmers and consumers. b) Level 1 marketing channels: breeders, wholesalers and consumers. c) Level 2 marketing channels: breeders, wholesalers, retailers and consumers. d) Level 3 marketing channels: breeders, wholesalers, collectors, retailers and consumers. The marketing cost in Boyolali Regency is at the zero level marketing channel, the total marketing cost is IDR3,000. The level 1 marketing channel is IDR11,606. The level 2 marketing channel is IDR9,606. The level 3 marketing channel is IDR6,060 From the results of the study, it can be concluded that the lowest marketing cost is the marketing cost on the zero marketing channel, which is IDR3,000. Low marketing costs mean that the marketing costs are marketing that effective.